HTML pocket reference - Niederst Robbins, Jennifer (O'Reilly, 2002)
"HTML Pocket Reference, 2nd Edition is a reference for any serious web designer, author, or programmer. Based on the best-selling Web Design In a Nutshell, the book includes updated information on every HTML tag and attribute, including browser support for Netscape Navigator, Internet Explorer, and Opera; and support for WebTV and HTML 4.01. You'll also find context for the tags and bare-bones examples of how standard web page elements are constructed. The book also includes useful charts of character entities and decimal-to-hexadecimal conversions."--Jacket.